2007
DOI: 10.1016/j.worlddev.2006.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Do Women’s Land Rights Promote Empowerment and Child Health in Nepal?

Abstract: SUMMARYWomen's land rights are increasingly put forth as a means to promote development by empowering women, increasing productivity, and improving welfare. However, little empirical research has evaluated these claims. This paper uses the 2001 Nepal Demographic and Health Survey to explore whether women's land rights empower women and benefit young children's health in Nepal. The results provide support for both of these hypotheses. Women who own land are significantly more likely to have the final say in hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
278
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 402 publications
(309 citation statements)
references
References 17 publications
10
278
1
1
Order By: Relevance
“…In fact, there has been a number of theoretical and empirical studies that focus on women's empowerment or empowerment of the poor and found positive well-being outcomes of increases in agency (e.g. Thomas, 1997;Hindin, 2000;Allendorf, 2007a;Kim et al 2007). In contrast, there is very little literature that considers empowerment outside of this gender context, which is the focus of our study.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there has been a number of theoretical and empirical studies that focus on women's empowerment or empowerment of the poor and found positive well-being outcomes of increases in agency (e.g. Thomas, 1997;Hindin, 2000;Allendorf, 2007a;Kim et al 2007). In contrast, there is very little literature that considers empowerment outside of this gender context, which is the focus of our study.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, more male were benefiting from 'cash for work' programme of WFP while more female were from 'food for work'. Allendorf (2007) stated that education played sustainable role for food security. In the region, education and skills among girls were limited due to the institutions of patrilocality.…”
Section: Resultsmentioning
confidence: 99%
“…The finding is consistent with study from Nepal which found that women who own land are significantly more likely to have the final say in household decisions (OR=1.48), a measure of empowerment. Similarly, children of mothers who own land are significantly less likely to be severely underweight (AOR=0.54) (23). On the other hand a study from Uganda found that land ownership exhibited no differentials with child stunting (24).…”
Section: Discussionmentioning
confidence: 98%